Rev-erb agonist SR9009 inhibits the proliferation of human colon cancer cell line HCT116 through reducing autophagy - SHI Guang, NING Na, HOU Xiao-hong, SUN Cong, YUAN Yuan, WANG Li, WANG Xiao-hui (Jichu yixue yu linchuang, 2020)
Objective To investigate the effect of hemeregulated nuclear receptor(Rev-erb) agonist SR9009 on the proliferation and potential mechanism of human colon cancer cell line HCT116. Methods HCT116 cells were cultured and treated with Rev-erb agonist SR9009 with proper dosagee and treatment time. The cell proliferation was observed with a phase contrast microscopve. The cell viability was tested using a CCK-8 kit. The mRNA transcription of Rev-erb α, Rev-erb β and autophagy genes Beclin1, LC3 and p62 were detected by real-time PCR. The protein expression of Rev-erb α, Rev-erb β, Beclin1, LC3 and p62 were detected by Western blot. Results 1)Rev-erb agonist SR9009 inhibited the HCT116 cell proliferation as compared with control group (P＜0.05), and the right dose of SR9009 was 20 μmol/L and the treatment time was 24 hours. 2)SR9009 significantly increased Rev-erb α and Rev-erb β mRNA transcription (P＜0.01) and protein expression (P＜0.05) in HCT116 cells. 3)R9009 significantly reduced the expression of autophagy genes Beclin1 and LC3 in HCT116 cells (P＜0.05), causing autophagy protein p62 accumulation. 4)HCT116 cell viability was further decreased with an autophagy inhibitor 3-methyladenine (3-MA) after SR9009 treatment (P＜0.05), the cell viability was restored by an autophagy activator rapamycin (P＜0.05). Conclusions Rev-erb agonist SR9009 inhibits proliferation and cell viability of colon cancer cell line HCT116 by reducing autophagy.